Seed Source Variation in Germination and Early Growth Among Ten Indigenous Populations of dalbergia sissoo Roxb. - Gera, Mohit; Gera, Neelu; Ginwal, H. S. (Indian Forester, 1999)
Ten provenances/seed sources of Dalbergia sissoo Roxb. Scattered over a vide range of its natural occurrence were studied for germination, nursery and early field performance. Significant variations among the provenances were observed in parameters, viz., germination per cent, seedling height and collar diameter, and field height and survival per cent. Variations for most of the traits studied were non-clinal type, except seed germination per cent, which showed significant negative correlation with altitude. Low germination among the seeds of higher elevation populations was found to be due to higher dormancy existing in these seedlots. The inverse relationship observed between seed germination percent and field height and collar diameter seems to be the result of poor germination due to dormancy existing in higher elevation seed sources. Such relationship may not be observed if the seeds are properly treated before sowing. The provenance T9 (Oachghat, Solan), Tl (Kukrail, Lucknow) and T4 (Orai, U.P.) were found to be more vigorous on the basis of field performance and can be used for meeting the immediate seed requirement for afforestation programmes.